Impact of high-speed rail on urban economic development: An observation from the Beijing-Guangzhou line based on night-time light images. (December 2020) - Guo, Yunxiang; Yu, Wenhao; Chen, Zhanlong; Zou, Renwei
Abstract: The high-speed rail (HSR) of China has developed and expanded rapidly and made great achievements in the past twenty years. The ongoing HSR plan is expected to have a significant impact on the urban economy and spatial structure in China. However, relevant data-driven research is still lacking. Traditional data collection approaches such as field surveys are costly to assure the accuracy of materials. In this study, a new remote sensing perspective of night-time light (NTL) was adopted to observe the long-term impact of the HSR on cities along the rail. More specifically, we investigated the impact of the Beijing–Guangzhou High-Speed Railway (BGHSR) on urban economic development by using night-time light data from 2002 to 2018. Such a line connects the capital (located in the north of China) and southern China and lies on the most important geographic axis of the country. Our results find that the construction of BGHSR line has a considerable positive impact on economies of first-tier cities (e.g., Beijing and Guangzhou) and new-first-tier cities (e.g., Zhengzhou, Wuhan, and Changsha), but also hurt some second-tier and third-tier cities such as Baoding and Handan. Generally, the spatial economic pattern of cities along the BGHSR line has been rapidly reshaped with the change of the transportation system. Each city needs to reconsider its role and value in the coming regionalization process to adapt to the national strategy. Highlights: A data driven method was used for analyzing the urban economic development. The impact of the Beijing–Guangzhou high-speed railway (BGHSR) on urban economic development was assessed. A policy suggestion was provided.